Evaluation of the activities of the juvenile court in the protection of abused and neglected students at the zonal social welfare agency in Ibadan, Nigeria (2002)
This study was carried out to evaluate the activities of the juvenile court in the protection o f abused and neglected children at the Zonal Social Welfare Agency in Ibadan, Nigeria. The major objective of the study was to find out if the goals for the establishment of the court are being met. The target population for the study was mostly children who had suffered from one form of abuse or the other. Fifty people were used as sample for the study. The method of data collection was through questionnaire administered personally by the researcher. Oral interviews were also conducted for both staff and the respondents. The responses collected, are scored and analyzed using chi-square statistics. Based on the findings, some recommendations were made on how well and how best the government can discourage child abuse and neglect through workshops, seminars, radio and television programmes.